(untitled) (Journal of Face Aesthetics, 2023)
Ladies and Gentlemen, it is with great pleasure that we would like to inform you that on November 24, 2023 (Friday) at the Poznan Univeristy of Medical Sciences, with the patronage of the JM Rector of the PUMS Prof. Andrzej Tykarski, the Supreme Chamber of Physicians, the Wielkopolska Chamber of Physicians and the City of Poznan, a Scientific and Training Conference „Weariness – its role and influence on facial appearance”. The conference theme includes a multi‑dimensional approach to the influence of weariness, the lack of sleep – the lectures will be presented by professors, specialists in one’s disciplines. In addition, legal aspects of facial aesthetics will be discussed. The conference is addressed to doctors, dentists and all those interested in facial aesthetics. We would like to invite all interested parties, including students, medical residents, postgraduate students, medical university for seniors, to participate in the conference during which the cooperation of researchers from various fields, as well as the discussion during the event will broaden the understanding of the concept of facial aesthetics. At the same time, we encourage all of you not only to participate in the conference but also to follow the research and scientific work in a multi‑specialty, interdisciplinary university journal that covers various aspects of facial aesthetics ”Journal of Face Aesthetics” published by the UMP Publishing House.